Chemokines: humble yet mighty players in the tumour microenvironment - Hima Xavier; Hima Xavier; Athira Gireesh Moly Gireesh; Juvin Ann Thomas; Priya Suboj; Priya Suboj; Arya Suresh; Arya Suresh; Emmanuel Biju; Arya Baby; Roshin Thomas Dominic; Suboj Babykutty; et al. (Frontiers in Immunology)
Chemokines are tiny chemotactic cytokines which play a crucial role in pathophysiology by maintaining homeostasis and inflammation. Their role in the tumour microenvironment is very much puzzling because of both pro- and anti-tumourigenic effects. Chemokines have gained much attention today, since it has been recognized that they are game changers in the TME via controlling immune cell recruitment, angiogenesis, metastasis, tumour growth and drug resistance. In this review, we are exploring the role of several chemokines and their receptors in the TME with special focus on immune cell recruitment, immune surveillance, regulation of immune checkpoints and epithelial mesenchymal transition. We are also reviewing the possibility of targeting chemokines along with immunotherapy for better outcome and disease-free survival. A better understanding on the dual role of chemokine in the TME might help to implement novel therapeutic interventions and adopt precision in targeted therapy.